Perchlorate-Coupled Carbon Monoxide (CO) Oxidation: Evidence for a Plausible Microbe-Mediated Reaction in Martian Brines - Myers, Marisa R.; King, Gary M. (Frontiers in Microbiology, 2017)
The presence of hydrated salts on Mars indicates that some regions of its surface might be habitable if suitable metabolizable substrates are available. However, several lines of evidence have shown that Mars’ regolith contains only trace levels of the organic matter needed to support heterotrophic microbes. Due to the scarcity of organic carbon, carbon monoxide (CO) at a concentration of about 700 ppm (about 0.4 Pa) might be the single most abundant readily available substrate that could support near-surface bacterial activity. Although a variety of electron acceptors can be coupled to CO oxidation, perchlorate is likely the most abundant potential oxidant in Mars’ brines. Whether perchlorate, a potent chaotrope, can support microbial CO oxidation has not been previously documented. We report here the first evidence for perchlorate-coupled CO oxidation based on assays with two distinct euryarchaeal extreme halophiles. CO oxidation occurred readily in 3.8 M NaCl brines with perchlorate concentrations from 0.01 M - 1 M. Both isolates were able to couple CO with perchlorate or chlorate under anaerobic conditions with or without nitrate as an inducer for nitrate reductase, which serves as a perchlorate reductase in extreme halophiles. In the presence of perchlorate, CO concentrations were reduced to levels well below those found in Mars’ atmosphere. This indicates that CO could contribute to the survival of microbial populations in hydrated salt formations or brines if water activities are suitably permissive.